2016
DOI: 10.1021/acs.bioconjchem.5b00561
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable Esterase-Activated Ca(II)-Sensitive MRI Contrast Agent

Abstract: Calcium [Ca(II)] is a fundamental transducer of electrical activity in the central nervous system (CNS). Influx of Ca(II) into the cytosol is responsible for action potential initiation and propagation, and initiates interneuronal communication via release of neurotransmitters and activation of gene expression. Despite the importance of Ca(II) in physiology, it remains a challenge to visualize Ca(II) flux in the central nervous system (CNS) in vivo. To address these challenges, we have developed a new generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…Structural modifications of metallic complexes influence cell uptake, and allow their utilization as probes for intracellular targets . For instance, some of these complexes can stain the lysosomes selectively, or can detect intracellular Ca 2+ . Previously, it was shown that several Tb and Eu complexes are capable of entering cells via macropinocytosis .…”
Section: Discussionmentioning
confidence: 99%
“…Structural modifications of metallic complexes influence cell uptake, and allow their utilization as probes for intracellular targets . For instance, some of these complexes can stain the lysosomes selectively, or can detect intracellular Ca 2+ . Previously, it was shown that several Tb and Eu complexes are capable of entering cells via macropinocytosis .…”
Section: Discussionmentioning
confidence: 99%
“…Lipophilicity measurements were performed using a previously described method [ 18 ]. GdL (3) was dissolved in water to a volume of 1 mL at a concentration of 1 mM and mixed with the same volume of 1-octanol.…”
Section: Methodsmentioning
confidence: 99%
“…35,36 Kim et al 34 (Figure 4). [43][44][45] Probes based on this mechanism have been used to monitor intracellular Ca (II) in hippocampal neuronal cells 43 and astrocytes. 44 The same OFF/ON strategy was used but using a Gd chelate modified for Ca (II) complexation linked to a dendrimer.…”
Section: Redox-responsive 1 H Mri Probesmentioning
confidence: 99%